Genetic variants associated with circulating C‐reactive protein levels and colorectal cancer survival: Sex‐specific and lifestyle factors specific associations. Issue 9 (13th January 2022) - Huang, Yuhan; Hua, Xinwei; Labadie, Julia D.; Harrison, Tabitha A.; Dai, James Y.; Lindstrom, Sara; Lin, Yi; Berndt, Sonja I.; Buchanan, Daniel D.; Campbell, Peter T.; Casey, Graham; Gallinger, Steven J.; et al.
Abstract: Elevated blood levels of C‐reactive protein (CRP) have been linked to colorectal cancer (CRC) survival. We evaluated genetic variants associated with CRP levels and their interactions with sex and lifestyle factors in association with CRC‐specific mortality. Our study included 16 142 CRC cases from the International Survival Analysis in Colorectal Cancer Consortium. We identified 618 common single nucleotide polymorphisms (SNPs) associated with CRP levels from the NHGRI‐EBI GWAS Catalog. Cox proportional hazards regression was used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for associations between SNPs and CRC‐specific mortality adjusting for age, sex, genotyping platform/study and principal components. We investigated their interactions with sex and lifestyle factors using likelihood ratio tests. Of 5472 (33.9%) deaths accrued over up to 10 years of follow‐up, 3547 (64.8%) were due to CRC. No variants were associated with CRC‐specific mortality after multiple comparison correction. We observed strong evidence of interaction between variant rs1933736 at FRK gene and sex in relation to CRC‐specific mortality (corrected P interaction  = .0004); women had higher CRC‐specific mortality associated with the minor allele (HR = 1.11, 95% CI = 1.04‐1.19) whereas an inverse association was observed for men (HR = 0.88, 95% CI = 0.82‐0.94). There was no evidence of interactions between CRP‐associated SNPs and alcohol, obesity or smoking. Our study observed a significant interaction between sex and a CRP‐associated variant in relation to CRC‐specific mortality. Future replication of this association and functional annotation of the variant are needed. Abstract : What's new? Chronic inflammation is strongly associated with colorectal cancer (CRC). C‐reactive protein (CRP) is a sensitive marker of this type of inflammation, and may be associated with poor prognosis. In this large genetic study, the authors found that none of over 600 CRP‐associated SNPs were associated with CRC‐specific mortality. However, they did identify a genetic variant of the FRK gene that may affect levels of CRP. This variant was associated with increased CRC mortality in women, while it showed the opposite effect in men. These findings may provide novel insights for improving CRC prognosis.